Asymmetric Dissociative Tunneling Ionization of Tetrafluoromethane in ω − 2ω Intense Laser Fields - Hasegawa, Hiroka; Walmsley, Tiffany; Matsuda, Akitaka; Morishita, Toru; Madsen, Lars Bojer; Jensen, Frank; Tolstikhin, Oleg I.; Hishikawa, Akiyoshi (Frontiers in Chemistry, 2022)
Dissociative ionization of tetrafluoromethane (CF_4) in linearly polarized ω-2ω ultrashort intense laser fields (1.4×10^{14} W/cm^2, 800 nm and 400 nm) has been investigated by three-dimensional momentum ion imaging. The spatial distribution of CF_^+ produced by CF_4 -> CF_3^+ + F + e^- exhibited a clear asymmetry with respect to the laser polarization direction. The degree of the asymmetry varies by the relative phase of the ω and 2$ω$ laser fields, showing that (i) the breaking of the four equivalent C-F bonds can be manipulated by the laser pulse shape and that (ii) the C-F bond directed along the larger amplitude side of the ω-2ω electric fields tends to be broken in the dissociative ionization. Weak-field asymptotic theory (WFAT) shows that the tunneling ionization from the 4t_2 second highest-occupied molecular orbital (HOMO-1) surpasses that from the 1t_1 HOMO. This predicts the enhancement of the tunneling ionization with electric fields pointing from F to C, in the direction opposite to that observed for the asymmetric fragment ejection. Possible mechanisms involved in the asymmetric dissociative ionization, such as the post-ionization interactions, are discussed.